2015
DOI: 10.1371/journal.pone.0127723
|View full text |Cite
|
Sign up to set email alerts
|

TaLHY, a 1R-MYB Transcription Factor, Plays an Important Role in Disease Resistance against Stripe Rust Fungus and Ear Heading in Wheat

Abstract: LHY (late elongated hypocotyl) is an important gene that regulates and controls biological rhythms in plants. Additionally, LHY is highly expressed in the SSH (suppression subtractive hybridization) cDNA library-induced stripe rust pathogen (CYR32) in our previous research. To identify the function of the LHY gene in disease resistance against stripe rust, we used RACE-PCR technology to clone TaLHY in the wheat variety Chuannong19. The cDNA of TaLHY is 3085 bp long with an open reading frame of 1947 bp. TaLHY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 33 publications
(29 reference statements)
1
43
0
Order By: Relevance
“…Further, no novel enriched motifs were detected in the aphid responsive genes using DREME and no motifs that were exclusively associated with the aphid-induced peroxidases could be identified; however, MYB2CONSENSUSAT and CURECORECR motifs were highly abundant in the promoters of the orthologue group of aphid responsive genes Sobic.002G416600, Pavir.Ba00167 and Si030339 and may be linked to their activation under periods of biotic stress. Several myb transcription factors induce gene expression under periods of biotic stress in grasses and activate networks of defencerelated pathways (Ibraheem et al 2015;Zhang et al 2015) and CURECORECR motifs are responsive to changes in oxygen levels and may be triggered by changes in ROS levels that often accompany insect feeding. Other regulatory elements that might induce the expression of all or a subset of the peroxidases in this interval include long range promoters or enhancers (Sanyal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Further, no novel enriched motifs were detected in the aphid responsive genes using DREME and no motifs that were exclusively associated with the aphid-induced peroxidases could be identified; however, MYB2CONSENSUSAT and CURECORECR motifs were highly abundant in the promoters of the orthologue group of aphid responsive genes Sobic.002G416600, Pavir.Ba00167 and Si030339 and may be linked to their activation under periods of biotic stress. Several myb transcription factors induce gene expression under periods of biotic stress in grasses and activate networks of defencerelated pathways (Ibraheem et al 2015;Zhang et al 2015) and CURECORECR motifs are responsive to changes in oxygen levels and may be triggered by changes in ROS levels that often accompany insect feeding. Other regulatory elements that might induce the expression of all or a subset of the peroxidases in this interval include long range promoters or enhancers (Sanyal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For qRT-PCR analysis, specific primers of eight stress-responsive genes (TaMYB73,TaABC1,TaOPR1,TaASR1,TaWRKY44,TaWRKY2,TaWRKY19,and TaCIPK29) were synthesized (Table 2S, supplement). Stress-associated genes in wheat plants were analyzed by qRT-PCR according to the method of Zhang et al (2015). SYBR Premix Ex Taq TM II Master (TaKaRa, Japan) was used for quantitative gene expression assays.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…This suggested that these disease resistance-related enzymes possibly contribute to greater disease resistance in the incompatible. As two important disease resistance genes in wheat, TaNIT and TaLHY may participate in regulating the defense response against stripe rust infection [47,48]. A previous study indicated that the expression of TaLHY was up-regulated after infection by CYR32 in Chuannong 19 with virus-induced gene silencing [48].…”
Section: Discussionmentioning
confidence: 99%
“…As two important disease resistance genes in wheat, TaNIT and TaLHY may participate in regulating the defense response against stripe rust infection [47,48]. A previous study indicated that the expression of TaLHY was up-regulated after infection by CYR32 in Chuannong 19 with virus-induced gene silencing [48]. We showed that infection by Pst could result in the up-regulated expression of TaNIT and TaLHY in CM42 (Figure 6), which suggests that these two genes may be involved in the defense response to stripe rust in wheat.…”
Section: Discussionmentioning
confidence: 99%